1998
DOI: 10.1080/10715769800300031
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in subjects affected by celiac disease

Abstract: In order to study the role of oxidative stress in celiac disease, protein carbonyl groups, thiobarbituric acid-reactive substance and pentosidine were evaluated in the plasma of nine patients with asymptomatic celiac disease and in a control group (n = 25). Plasma alpha-tocopherol, retinol and lipids were determined in the same samples. The levels of markers of oxidative stress derived from both protein (carbonyl groups) and lipids (thiobarbituric acid-reactive substances) were significantly higher in celiac d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 24 publications
4
32
0
Order By: Relevance
“…Using thiobarbituric acid -reactive substances as a marker of OS, Odetti et al 12 showed that redox equilibrium is impaired in patients with CD. They also observed decreased serum α -tocopherol levels in a group with silent CD in comparison with controls.…”
Section: Methodsmentioning
confidence: 99%
“…Using thiobarbituric acid -reactive substances as a marker of OS, Odetti et al 12 showed that redox equilibrium is impaired in patients with CD. They also observed decreased serum α -tocopherol levels in a group with silent CD in comparison with controls.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that 97% of subjects with CD contain class II HLA genetic markers, predominantly HLA-DQ2, on chromosome 6p21 (Stojiljković et al, 2007). Another study (Odetti et al, 1998), revealed that in 40% of the population, the presence of this haplotype is essential for the development of CD and lack of these alleles, therefore, eliminates the diagnosis. Tosi et al (1983) found DQ2, especially in combination with HLA-DQA1*0501 and HLA-DQB1*0201, together coding for the HLA-DQ2 (A1*0501, B1*0201) heterodimer as the major determinant in the development of CD.…”
Section: Discussionmentioning
confidence: 99%
“…Taking oxidative stress into consideration, Odetti et al (1998) used TBARS as an indicator of oxidative stress in their research to ultimately observe that redox equilibrium is impaired in CD and, consequently, causes the severe deterioration of proteins and lipids. Kiss et al (1997) reported that in CD a markedly increased activity in SOD exists, whereas the activity of GSH-Px significantly decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a few investigations indicate that the AO capacity of celiac patients is diminished. Odetti et al (1998) found a lowered level of vitamin E and increased levels of markers of oxidized lipids and proteins in the plasma of celiac patients subjected to gluten free diet, while Ståhlberg et al have reported decreased GSH concentrations and GPx activity in erythrocytes and the small intestinal mucosa of children affected by celiac disease (Ståhlberg et al, 1988;Ståhlberg & Hietanen, 1991). In our previous papers (Stojiljković et al, 2007;Stojiljković et al, 2009) we showed that oxidative stress is strongly associated with CD and that the AO capacity of celiac patients is weakened by a depletion of GSH and reduced activities of GSHdependent AO enzymes GPx and GR.…”
Section: Oxidative Stress and Antioxidant Status Of Patients With Celmentioning
confidence: 99%